Nurses’ Knowledge and Practices Regarding Prevention of Cesarean Section Wound Infection: An Intervention Program (International Journal of Nursing Education, 2026)
Aim: study the effect of educational program on nurses' knowledge and practices regarding prevention of caesarean section wound infection. Setting: The study was conducted in Obstetrics and Gynecology Department at Farasan General Hospital. Design: A Quasi-experimental study (pre and post-test) was utilized. Sampling: Convenient sample included 50 nurses. Tools: Two tools were used Self-administered questionnaire and Observational checklist. Results: majority of studied nurses had poor total knowledge score regarding prevention of caesarean section wound infection pre intervention. While most of them had good total knowledge score regarding prevention of caesarean section wound infection post intervention. More than majority of studied nurses had unsatisfactory total practices pre intervention toward prevention of caesarean section wound infection , meanwhile  majority of them  had high satisfactory total practices post intervention.. Conclusion: the intervention program had positive effect on nurses' knowledge and practices regarding prevention of caesarean section wound infection after application of program compared to before application. Recommendations: Updating knowledge and practices of nurses through continuous in-service educational programs emphasizing the importance of the evidence-based practices of prevention of caesarean section wound infection.
Keywords: Educational program, nurses' knowledge and practices, caesarean section wound infection.